Effect of Various Development Periods on Accumulation of Some Mineral Elements on the Leaves of Strawberry Cultivars (Fragaria X ananassa Dutch. L) - YILMAZ, HUDAI; MURADOGLU, FERHAT; YILDIZ, KENAN (Asian Journal of Chemistry, 2010)
An experiment has been set up with Tudla, Muir, Douglas,Rupella, Moraline, Evita, Aiko, Northeastern, Tioga, Elvira andDelmarvel cultivars for mineral accumulations of nitrogen,phosphorus, potassium, calcium, magnesium, manganese, zinc,copper, iron and boron on plants' leaves were analyzed in threedifferent periods which are fruit formation (May 26th), stolonformation (July 13th) and beginning of resting period (September27th). It was determined that generally mineral elements accumulationchange in relation to development periods. In addition, theperiodic change in nitrogen, potassium, manganese, zinc, copperand boron minerals were more evident. No clear change was seenin phosphorus and calcium. Despite that changes were seen in ironmineral at the cultivar level, this situation did not present itself ingeneral averages. When every cultivar is analyzed by itself, therewere clear differences among cultivars. Every cultivar's mineralelement accumulation level has shown variation. Differences amongcultivars' averages have been found statistically significant.